Enhanced production of recombinant HALT-1 pore-forming toxin using two-step chromatographic procedure - Yap, Wei Yuen *; Loo, Lok Wenn; Sha, Hong Xi; Hwang, Jung Shan * (Elsevier, 2023)
Hydra actinoporin-like toxin-1 (HALT-1) has been isolated from Hydra magnipapillata and is highly cytolytic against various human cells including erythrocyte. Previously, recombinant HALT-1 (rHALT-1) was expressed in Escherichia coli and purified by the nickel affinity chromatography. In this study, we improved the purification of rHALT-1 by two-step purifications. Bacterial cell lysate containing rHALT-1 was subjected to the sulphopropyl (SP) cation exchange chromatography with different buffers, pHs, and NaCl concentrations. The results indicated that both phosphate and acetate buffers facilitated the strong binding of rHALT-1 to SP resins, and the buffers containing 150 mM and 200 mM NaCl, respectively, removed protein impurities but retain most rHALT-1 in the column. When combining the nickel affinity chromatography and the SP cation exchange chromatography, the purity of rHALT-1 was highly enhanced. In subsequent cytotoxicity assays, 50% of cells could be lysed at ∼18 and ∼22 µg/mL of rHALT-1 purified with phosphate and acetate buffers, respectively. • HALT-1 is a soluble α-pore-forming toxin of 18.38 kDa.